Tetrakis{2-[N-((3-morpholino)propyl)carbamateloxyethyl} zinc(II) phthalocyanine and its water soluble derivatives: Synthesis, photophysical, photochemical and protein binding properties - Colak, Senem; Durmuş, Mahmut; Yildiz, Salih Zeki (Elsevier Science Sa, 2016)
In this study, the novel water soluble derivatives of 2-[N-((3-morpholino)propyl)carbamate]oxyethyl substituted zinc(II) phthalocyanine (1) bearing different type of groups such as sulfobetaine (2), betaine (3), N-Oxide (4) and quaternized methyl (5) on the morpholine core were synthesized for the first time. All newly synthesized zinc(II) phthalocyanine derivatives were characterized by different spectroscopic techniques such as UV-vis, FT-IR, H-1 NMR, mass and elemental analysis as well. They showed excellent solubility in aqueous media due to their zwitterionic and ionic characters which makes them promising candidates for treatment of cancer by photodynamic therapy (PDT). The photophysical and photochemical properties were investigated in DMSO for tetrakis(2-[N-((3-morpholino)propyl)carbamate]oxyethyl} substituted zinc(II) phthalocyanine (1) and in both DMSO and water+Triton X-100 solutions for its water soluble ionic derivatives (2-5). The binding behaviors of ionic zinc(II) phthalocyanines by bovine serum albumin (BSA) protein were investigated for determination of transportation ability of these phthalocyanines in the blood circulation. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Ionic; Zwitterionic; Fluorescence; Singlet oxygen